2019
DOI: 10.12982/cmujns.2019.0007
|View full text |Cite
|
Sign up to set email alerts
|

Autolysis of Clown Featherback (Chitala ornata) Muscle

Abstract: Clown featherback (Chitala ornata) is a freshwater fish important in the cuisine of Thailand and other Southeast Asian countries. It has a short marketable life due mainly to poor gelling characteristic even when stored in ice. This deterioration has been associated with muscle autolysis. The research was aimed to investigate the autolysis of clown featherback muscle (CFM). To test autolysis, mince from CFM was incubated in atemperature controlled water bath for 60 min at 5, 10, 20, 30, 40, 50, 60, 65, 70, 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…It indicated that the activation of enzyme activity in beardless barb muscle occurred at both acidic and alkaline pH values, which were further responsible for the autolysis of fish. Autolysis of clown featherback mince is due to a heat‐activated proteinase active at both acidic and alkaline pH values (Thiabmak et al ., 2019). Maximum autolytic activity of tilapia surimi was found at 65 °C (Yongsawatdigul et al ., 2000).…”
Section: Resultsmentioning
confidence: 99%
“…It indicated that the activation of enzyme activity in beardless barb muscle occurred at both acidic and alkaline pH values, which were further responsible for the autolysis of fish. Autolysis of clown featherback mince is due to a heat‐activated proteinase active at both acidic and alkaline pH values (Thiabmak et al ., 2019). Maximum autolytic activity of tilapia surimi was found at 65 °C (Yongsawatdigul et al ., 2000).…”
Section: Resultsmentioning
confidence: 99%